Effectiveness of acupressure therapy in lowering blood pressure in patients with hypertension: A systematic review - I Gede Restawan; Elly Lilianty Sjattar; Andi Masyitha Irwan (Elsevier, 2023)
Introduction: Hypertension is still a major global health problem and causes serious complications. Pharmacological therapy has been proven in lowering blood pressure, but non-compliance often occurs and causes side effects. A combination of non-pharmacological therapies, such as acupressure therapy, is important. This study aimed to describe and systematically assess the types of acupoints, benefits, and duration of acupressure therapy on the blood pressure in patients with hypertension. Methods: A systematic literature search was conducted on seven databases, namely, PubMed, DOAJ, Science Direct, ProQuest, CINAHL-EBSCO, Cochrane Library, and Garuda, to identify studies published based on the following inclusion criteria: articles published in English and Indonesian in the last 10 years (2012-2022), articles that employed a quantitative research design, i.e., RCTs and quasi-experimental, articles that mainly focus on acupressure and lowering blood pressure in patients with hypertension, and the study participants were 18 years old. Meanwhile, the exclusion criteria were as follows: the study population was composed of pediatric patients, articles not published in English and Indonesian, studies that were not intervention types, not in the objectives of the study, article in review form, study not full text. This systematic review uses the PRISMA guidelines by protocol registration number (PROSPERO) CRD42022368979, Critical Appraisal Skill Program (CASP) for randomized controlled trials, and Quasi-Experimental Checklist (JBI version) in assessing article quality. This research did not receive any specific grant from funding agencies in the public, commercial, or not-for-profit sectors. Result: A total of 3.376 articles were screened, of which nine studies were eligible for analysis. Two articles recommended the application of acupoints, namely, the Taichong (LR3), Shenmen (HT7), and Taixi (KI3) acupoints, which are effective in lowering blood pressure. The duration of acupressure administration was reported to range from 3 to 40 min, and each duration can decrease blood pressure. The maximum result in lowering blood pressure in the physiological adaptation process can be achieved in 4 weeks. Conclusion: Acupressure therapy at Taichong (LR3), Shenmen (HT7), and Taixi (KI3) acupoints is a good non-pharmacological therapy option to help in lowering blood pressure in patients with hypertension.